Acoustic Sensors and Their Applications - Sattar, Farook; Puhan, Niladri Bihari; Fazel-Rezai, Reza (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Acoustic sensors have been utilized commercially for more than 60 years. Acoustic sensing technologies have been studied extensively and the information, transmission, reception, transformation, processing, and application of acoustic signals have been developed, with acoustic sensors as the central focus. An acoustic sensor is a device that converts a sound wave signal into an electrical signal. This Special Issue on Acoustic Sensors and Their Applications presents original research covering recent advances in all aspects of the design, development, testing, and application of acoustic sensors.